Elderly people's choice of media and their perceived state of loneliness - Öngün, Erdem; GUDER, FERİDE ZEYNEP; Demirağ, Aşkın (My University, 2016)
This study aims at finding the relationship between elderly people's perceived state of loneliness and their choice of (old and/or new) media instruments. The sample of the study consists of randomly selected 300 elderly people over 60 who reside in rest homes in two different cities, Hatay and Istanbul in Turkey. Participants were given a questionnaire with three sections. The first section included questions related to the participants' demographic characteristics. Adapted from Russell's (1996) "Loneliness Scale (Version 3)", the second part was related to participants' perceived state of loneliness. Final section was about their choice of media and related details such as aim and time spent on them. Analyzed by statistical methods, study findings show that elderly people from two different social settings and with changing demographic features display differing degrees of loneliness with a significant relationship between the forms of media they used, their related choices, aims and perceived state of loneliness.
Keywords: Elderly People; Loneliness; Rest Homes; Media; Traditional Media; New Media; Yaşlı İnsanlar; Yalnızlık; Huzur Evleri; Medya; Geleneksel Medya; Yeni Medya